2013
DOI: 10.1002/micr.22129
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery for groin lymphocele and lymphedema after oncologic surgery

Abstract: Groin lymphocele (GL) is a frequent complication of inguinal lymph node dissection, and conservative treatment is not always successful. Different surgical methods have been used to treat lymphoceles arising from lymphatics injured during groin surgery. However, they all involve the closure of lymphatics merging at the lymphocele, increasing the risk of postoperative lower limb lymphedema or of worsening lymphedema if already clinically evident. We assessed the efficacy of a diagnostic and therapeutic protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 16 publications
(35 reference statements)
3
31
0
2
Order By: Relevance
“…Not only are our favorable outcomes in line with results from the literature (Boccardo et al, ; Todokoro et al, ; Yamamoto et al, , ), but our report has also several added values. We described the largest series of patients suffering from secondary lymphorrhea successfully treated by lymphaticovenous anastomosis to date.…”
Section: Discussionsupporting
confidence: 91%
“…Not only are our favorable outcomes in line with results from the literature (Boccardo et al, ; Todokoro et al, ; Yamamoto et al, , ), but our report has also several added values. We described the largest series of patients suffering from secondary lymphorrhea successfully treated by lymphaticovenous anastomosis to date.…”
Section: Discussionsupporting
confidence: 91%
“…9 Besides functional impairment, lymphedema also significantly jeopardizes the patients' quality of life. 10,11 Once it becomes clinically evident, lymphedema responds poorly to treatment and tends to worsen progressively, causing irreversible fibrotic changes of the tissue. 12 Moreover, erysipelas episodes frequently complicate chronic extremity lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of supermicrosurgical D‐LVA. Some authors reported deep lympho‐venous bypass, but they use lymphatic vessels in deep fat layer that are lymphatic vessels of a superficial lymph system . Deep lymphatic vessels as we used in this case are lymphatic vessels of a deep lymph system that exist below the deep fascia.…”
Section: Discussionmentioning
confidence: 99%